IMPLEMENTATION OF WI-FI BASED INTERNET NETWORK CONNECTION AND TRAINING FOR TEACHERS OF STATE VOCATIONAL SCHOOL 1 LINTONG NI HUTA - Bambang (Jurnal Prinsip Pengabdian Masyarakat, 2025)
Computer networks are needed in various fields, including in schools. Computer networks are needed for the efficiency and effectiveness of cost and equipment use. SMK Negeri 1 Lintong Ni Huta, one of the State Vocational Schools in Humbang Hasudutan Regency, as an IT-based Vocational School or one that manages the RPL and TKJ Departments, should utilize Computer Networks as a means and infrastructure in the teaching and learning process and services to students. However, in reality, this has not been implemented due to a lack of understanding and not understanding the function and advantages of a computer network. That is the reason why it is important to carry out this community service at SMK Negeri 1 Lintong Ni Huta.